LE BON SAMARITAIN: UN EXEMPLE AU SERVICE DE LA DIGNITE HUMAINE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The Good Samaritan:An example at the service of human dignityThe parable of the Good Samaritan is one of the best-known and most fascinating stories told by Jesus in order to make understand a “doctor of the Law” and to every man of good will what it means the neighbour and the way in which we must rescue him and to come for help him. The fundamental biblical principle for this is the creation of man according to the image and likeness of God. In this communication, in the first part we will present some interpretations of the parable in the history of the Church, and in the second part, we will highlight some theological aspects and political implications for a fair life in society and in the Church, founded on the love of God as a gift to salvation of dignity of humankind in Jesus Christ.